Prevalence and risk factors of musculoskeletal pain symptoms as long-term post-COVID sequelae in hospitalized COVID-19 survivors: a multicenter study. Issue 9 (10th September 2022) - Fernández-de-las-Peñas, César; de-la-Llave-Rincón, Ana I.; Ortega-Santiago, Ricardo; Ambite-Quesada, Silvia; Gómez-Mayordomo, Víctor; Cuadrado, María L.; Arias-Navalón, José A.; Hernández-Barrera, Valentín; Martín-Guerrero, José D.; Pellicer-Valero, Oscar J.; Arendt-Nielsen, Lars
Abstract : The prevalence of long-term musculoskeletal post-COVID pain was 45.1% with female sex, history of musculoskeletal pain, the presence of myalgia and headache as onset symptoms, and days at hospital as risk factors. Abstract: This study investigated the prevalence of long-term musculoskeletal post-COVID pain and their risk factors in a large cohort of COVID-19 survivors. A multicenter cohort study including patients hospitalised because of COVID-19 in 5 hospitals of Madrid (Spain) during the first wave of the pandemic was conducted. Hospitalisation and clinical data were collected from medical records. Patients were scheduled for a telephone interview after hospital discharge for collecting data about the musculoskeletal post-COVID pain. Anxiety/depressive levels and sleep quality were likewise assessed. From 2000 patients recruited, a total of 1969 individuals (46.4% women, age: 61 years, SD: 16 years) were assessed on average at 8.4 (SD: 1.5) months after discharge. At the time of the study, 887 (45% women) reported musculoskeletal post-COVID pain. According to the presence of previous pain symptoms, the prevalence of "de novo" (new-onset) musculoskeletal post-COVID pain was 74.9%, whereas 25.1% experienced an increase in previous symptoms (exacerbated COVID-related pain). Female sex (odds ratio [OR]: 1.349, 95% confidence interval [CI]: 1.059-1.720), history of musculoskeletal pain (OR 1.553, 95% CI 1.271-1.898), presence of myalgia (OR 1.546, 95% CI 1.155-2.070) and headache (1.866, 95% CI 1.349-2.580) as COVID-19–associated onset symptoms, and days at hospital (OR 1.013, 95% CI 1.004-1.022) were risk factors associated with musculoskeletal post-COVID pain. In conclusion, musculoskeletal post-COVID pain is present in 45.1% of COVID-19 survivors at 8 months after hospital discharge with most patients developing de novo post-COVID pain. Female sex, history of musculoskeletal pain, presence of myalgia and headache as COVID-19 symptoms at the acute phase, and days at hospital were risk factors associated with musculoskeletal post-COVID pain.